The Collaboration of Zakat and CSR in Improving Access to Clean Water in Gunungkidul Regency - Resti Mirza Apriani (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study examines the collaboration between the National Board of Zakat (BAZNAS) and three corporate partners through Corporate Social Responsibility (CSR) schemes in providing clean water access across five water-scarce villages in Gunungkidul Regency. Using a qualitative case study approach, the research is based on in-depth interviews, field observations, and program documentation. The findings reveal that the integration of zakat and CSR not only succeeded in the physical construction of bore wells but also fostered active community participation in water management. Within Austin’s Collaboration Continuum framework, the partnership demonstrates an integrative phase characterized by shared roles, responsibilities, and mutual values. Furthermore, through Gleick’s perspective, the program fulfills the principles of water equity, social efficiency, and ecological sustainability. This initiative reached more than 600 households through an approach that responds to basic needs while strengthening local community resilience. These results suggest that zakat–CSR collaboration holds significant potential as an alternative social financing model for basic infrastructure development in ecologically vulnerable regions.